Relationship between authors' structural position in the collaboration network and research productivity: Case of Indian earth scientists. Issue 4 (27th August 2014) - Kumar, Sameer; Mohd. Jan, Jariah
Abstract : Purpose: – The purpose of this paper is to compute and analyze the topological properties of co-authorship network formed between earth scientists in India. As a case study, the authors evaluate bibliographic data of authors who have contributed research articles in the Journal of the Geological Society of India, a premier earth science journal in India. Design/methodology/approach: – Research articles totaling 3, 903 records from 1970 to 2011 were harvested from the ISI Web of Science SCI database and analyzed using Social Network Analysis. Findings: – The author productivity in terms of number of papers published followed Lotka's law with β =2.1027. A dense giant component was detected that spanned 73 percent of the network with a density of 0.0017 and clustering coefficient of 0.631, suggesting high level of knowledge diffusion and a rapid flow of information and creativity in this network. Local metrics were calculated using degree, betweenness and closeness centralities. A strong correlation was seen between degree and author productivity (number of works) and betweenness centrality and author productivity, suggesting that author's number of connections and controlling "in-between" position in the network may be providing the authors' with the knowledge and resources to be more productive. Originality/value: – The impact of human actions on the earth systems is a hot topic of research in India. This is one of the first works that investigates co-authorship networks of Indian earth science researchers.